Quem disse que não se pode ensinar estatística nos anos iniciais do ensino fundamental? contribuições de professores que ensinam Matemática em encontros compartilhados de formação - Marcelo Pereira Rizzi (2023)
This research seeks to contribute to the continuing education of teachers who teach Mathematics in the Early Years of Elementary School with regard to the Teaching of Statistics, through shared training meetings, valuing and re-signifying knowledge acquired in their academic and professional careers. In the course of this research, we sought to focus on the following research question: What conceptions and resignifications do teachers have in relation to the teaching and learning of Statistics in the Early Years of Elementary School? In view of this investigative question, the general objective of this dissertation is to investigate conceptions, elements of memories and knowledge related to the teaching of Statistics that were mobilized and re-signified in a collaborative context with teachers who work in the Early Years of Elementary School. As specific objectives we present: (1) to discuss aspects of the Statistics curriculum to be worked on in the Early Years of Elementary School (1st to 5th year), considering current curricular documents; (2) to exemplify proposals for the classroom that allow working on initial notions of Statistics through activities that propose the protagonism of the teacher who works in the Early Years of Elementary School, aiming at continuing education and (3) to constitute a collaborative context of training with teachers who teach Mathematics in the Early Years of Elementary School. Regarding the methodology, its development was carried out in a qualitative approach, seeking to value the following data: detailed description of situations, contexts, people, interactions, behaviors, teachers' speeches, attitudes, conceptions, among others; relevant aspects that ensure the commitment to the production of knowledge. The fieldwork plan comprised virtual training meetings shared with teachers who teach Mathematics and who were interested in the topic of Teaching Statistics in the Early Years of Elementary School. It is worth highlighting that these meetings took place in a collaborative work perspective, valuing, in particular, mutual respect and reciprocity of learning. The instruments for recording information consisted of the speeches of all teachers in each meeting carried out through an audio and video recording program, in addition to responses to questionnaires prepared and transmitted via e-mail to the participants of the meetings. As a final product, based on the references worked, we created dialogues with teachers during shared training meetings and records written on forms, an e-book aimed at professionals who teach Mathematics in the Early Years of Elementary School, in order to collaborate with the teaching work , responding to the main questions that basic education teachers may have about this topic. In short, an e-book designed with teachers, for teachers.